EVALUATION OF THE INTEGRATED POPULATION COURT PROGRAM IN COLLABORATION WITH THE DISTRICT COURT (SEDU KOPI) AT THE POPULATION AND CIVIL REGISTRATION SERVICE IN BENER MERIAH - Rizaldi Win Arif; Aiyub; Arinanda (RADJA PUBLIKA, 2025)
This study aims to evaluate the Integrated Population Court Collaboration with the District Court (SEDU KOPI) Program implemented by the Population and Civil Registration Office of Bener Meriah Regency. This program is a form of public service innovation that aims to facilitate the public in processing population documents that require court decisions, such as name changes, birth certificate corrections, child recognition, and adoption, without having to come directly to the courthouse. This study uses a qualitative method with data collection techniques through interviews, observation, and documentation. Data analysis was conducted using William N. Dunn's public policy evaluation theory, which emphasizes three main indicators, namely effectiveness, efficiency, and equity. The results of the study indicate that the SEDU KOPI program is quite effective in providing convenience to the public because it shortens service time and increases access to population legal services. However, its implementation has not been optimal due to several obstacles, such as a minimal implementation budget, lack of socialization to the public, a low number of incoming applications, and a limited number of assigned judges. This condition resulted in irregular program implementation and even stopped. Based on the evaluation results, it can be concluded that the SEDU KOPI program is a beneficial and relevant innovation in improving the quality of population administration services. However, to ensure the program's sustainability, adequate budget support, improved inter-agency coordination, and intensified community outreach are needed to optimally achieve the program's primary objectives.